VDC_100102372205.0X000001. Issue 11 (November 2019) - Zendel, Alex; Mor, Eyal; Goitein, David; Hazzan, David; Nissan, Aviram; Zippel, Douglas
Although elective laparoscopic cholecystectomy is the accepted strategy after endoscopic retrograde cholangiopancreatography (ERCP), papillotomy, and common bile duct (CBD) clearance, the decision to perform a cholecystectomy in high-risk elderly comorbid patients remains subjective and is controversial. The aim of this study was to examine the outcome of elderly patients with cholecystectomy deferral after successful initial endoscopic removal of CBD stones. The study examined a retrospective patient database, which included all patients aged >60 years who underwent an ERCP for CBD stones at the Chaim Sheba Medical Center. The study cohort was divided according to whether a subsequent cholecystectomy was performed and also by age 60 to 80 or >80 years. All biliary-related complications were recorded. The primary outcome measures were biliary complications, perioperative and periprocedural mortality, CBD stone recurrence, and the need for future surgical intervention. There were 111 patients (mean age 79.4 ± 9.1 years) who underwent ERCP with follow-up. After excluding 11 patients, 100 patients were left for analysis, 46 of whom underwent a cholecystectomy and 54 were observed without operation. There were significant longer term biliary complications in five of the operated patients (10.9%) and in four of the unoperated cases (7.4%). All biliary-related complications were managed successfully by conservative means except for one fatality in the nonoperated group. Biliary-related complications after successful ERCP for CBD stones were unaffected by surgery but were more commonly observed in older cases. A watch and wait policy may be justified in elderly comorbid patients.